Rodzina ważnym środowiskiem w rozwoju muzycznym dziecka = Family as an important environment in musical development of a child - Kumik, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The family is an environment that most fully meets the needs of a child, give it the best care and the most favourable conditions for development. A family has a huge influence on the attitudes and needs of a child, and also the way of their fulfilment. The requirements that a child faces within a family affects also the development of skills and abilities and the level of personal achievements.
Keywords: rodzina; formy aktywności muzycznej; rozwój muzyczny dziecka; family; family environment; musical development of a child